Between Business Capital and Daily Needs: Utilization of PNM Mekaar Funds in Jorong Pinang Makmur, Dharmasraya Regency - Rinel Fitlayeni; Sri Rahayu; Lenny Shophiana; Abimayu Andika Santosa (Jurnal Mamangan, 2025)
Permodalan Nasional Madani (PNM) is a state-owned financial institution that focuses on empowering underprivileged women through the Mekaar program. This program is expected to serve as initial capital for communities to improve their welfare through small-scale business activities. However, in practice, the utilization of loan funds does not always align with the initial objectives, as most beneficiaries tend to use the loans to meet daily household needs. This phenomenon is particularly interesting to study in Jorong Pinang Makmur, Timpeh Sub-district, Dharmasraya Regency. This study aims to examine the patterns of PNM Mekaar fund utilization by members, as well as to analyze the socio-economic dynamics that influence their decisions in managing these funds. Using a descriptive qualitative approach through interviews and observations, a total of 31 informants consisting of members and PNM account officers were analyzed using Max Weber's social action theory. Based on the results of the study, it can be concluded that the majority of members use the loan funds for daily consumption and children's education (92%), while only a small portion (8%) use it for its intended purpose as business capital. This pattern of fund utilization is influenced by the economic pressures of underprivileged households, low financial literacy, limited business opportunities, and local socio-economic conditions. This phenomenon reflects Weber's form of social rationality, in which members' economic actions are not only driven by capitalist productive logic but also by instrumental goals, value orientations, and social norms to maintain the group's survival and honor. Thus, the utilization of PNM Mekaar funds in the research location functions more as a means of supporting basic needs than as a means of developing productive businesses, which implies the need for program evaluation in a social context.